Post-Partum Factor VIII Inhibitors - Hauser, I; Schneider, B; Lechner, K (Thrombosis and Haemostasis, 1995)
In a retrospective study 51 published cases of post-partum factor VIII inhibitors were analyzed with regard to the outcome according to treatment. The overall outcome was favorable with 97% survival at two years. The probability of complete remission (CR, absence of the inhibitor and normalization of factor VIII activity) was almost 100% at 30 months. Steroid treatment appears to be not superior to no treatment, but patients treated with immunosuppressive drugs (cyclophosphamide, azathioprine, 6-mercaptopurine) had a significantly shorter time to CR. In the absence of a randomized trial this analysis may be helpful for decision-making in women with factor VIII post-partum inhibitors. Because of the retrospective study design, conclusions have to be regarded with caution.